Karakteristik Spasial Data Hotspot MODIS Tahun 2019 Di Kota Palangka Raya Provinsi Kalimantan Tengah: Spatial Characteristics of MODIS Hotspot Data in 2019 in Palangka Raya City, Central Kalimantan Province - Andre Pinem; Santosa Yulianto; Rini Dwiastuti (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2022)
Forest and land fires in Palangka Raya City are events that almost occur every year during the dry season, forest and land fires in 2015 were recorded as one of the worst incidents in recent years. Fires in Palangka Raya City during the period January – August 2019 reached approximately 1222 hectares. The aim of the researcher to load the spatial data above is to help complete the data and be a reference in researching the spatial characteristics of the 2019 MODIS hotspot data in Palangka Raya City by examining the spatial characteristics of the MODIS hotspot data to predict forest and land fires, as well as to provide the latest information on hotspots. hotspots and the location of hotspots that need to be watched out for. The method used in this study is a combination of spatial analysis and fieldwork to obtain an overview of the spatial characteristics of the spatial data. The results of this study show that the distribution of MODIS hotspots in 2019 in the city of Palangka Raya is highest in the Sabangau sub-district while the lowest is in the Bukit Batu sub-district, with high and medium confidence levels, during a prolonged dry season and due to land clearing activities by burning. The characteristics of the MODIS hotspot in the city of Palangka Raya have 21 spatial characteristics in general consisting of vegetation types in the form of broadleaf acacia plants at sapling level, shrubs, conversion of agricultural land, and housing with road, river and peat distribution accessibility in the city of Palangka Raya.